The Effectiveness Massage Therapy on Motoric Status among Non-Hemorrhagic Stroke Patients - Iga Kurnia Rohmah Rohmah (International Journal of Nursing and Health Services (IJNHS), 2021)
Background – Stroke is the third largest cause of disability globally, representing a high economic and social burden on society. Objectives - The study aimed to determine the effectiveness of massage therapy on motor status among non-hemorrhagic stroke patients. Method – This study was a literature review. The article was searched using Science Direct, PubMed, Elsevier, Garuda Portal, Pro-quest, EBSCO, National Library, Google Scholar. The term keywords were massage, aromatherapy, motor status, stroke patients. Results – A total of 25 journals from 7,747 published journals were identified based on inclusion and exclusion criteria. This shows massage therapy was an intervention that can be applied to improve motor status in non-hemorrhagic stroke patients and does not cause harmful effects to be carried out as an intervention. Conclusion – The focus form of the intervention provides feedback or information that can be on motor status. Intervention in the form of massage therapy is one of the complementary therapies that can be used by health professionals in handling and improving motor status in non-hemorrhagic stroke patients.